2021
DOI: 10.1038/s41598-021-86975-9
|View full text |Cite
|
Sign up to set email alerts
|

The PsbS protein and low pH are necessary and sufficient to induce quenching in the light-harvesting complex of plants LHCII

Abstract: Photosynthesis is tightly regulated in order to withstand dynamic light environments. Under high light intensities, a mechanism known as non-photochemical quenching (NPQ) dissipates excess excitation energy, protecting the photosynthetic machinery from damage. An obstacle that lies in the way of understanding the molecular mechanism of NPQ is the large gap between in vitro and in vivo studies. On the one hand, the complexity of the photosynthetic membrane makes it challenging to obtain molecular information fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 59 publications
1
37
0
Order By: Relevance
“…VDE converts the violaxanthin pool to zeaxanthin which may lead to violaxanthin-zeaxanthin exchange in the loose, peripheral xanthophyll-binding site of LHCII (Xu et al, 2015 ). It has been shown that the presence of zeaxanthin affects the kinetics and amplitude of NPQ but is not a strict requirement for it (Ruban and Horton, 1999 ; Nicol and Croce, 2021 ). Quenching can similarly be achieved in the absence of PsbS if ΔpH is driven to non-physiological levels (Johnson and Ruban, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…VDE converts the violaxanthin pool to zeaxanthin which may lead to violaxanthin-zeaxanthin exchange in the loose, peripheral xanthophyll-binding site of LHCII (Xu et al, 2015 ). It has been shown that the presence of zeaxanthin affects the kinetics and amplitude of NPQ but is not a strict requirement for it (Ruban and Horton, 1999 ; Nicol and Croce, 2021 ). Quenching can similarly be achieved in the absence of PsbS if ΔpH is driven to non-physiological levels (Johnson and Ruban, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…First, energy-dependent quenching, qE, is turned on rapidly by an increase in thylakoid lumen proton concentration, followed by protonation of the thylakoid membrane protein, photosystem II (PSII) subunit S (PsbS) [ 6 ], and reversible conversion of xanthophyll pigments. qE follows the variations of the transmembrane proton gradient (ΔpH), thus its induction and relaxation typically develop within a few minutes (1–3 min) [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lifetimes of pigment-protein complexes largely depend on their local environment, e.g. detergent or proteoliposome (41)(42)(43). The density of the micelles containing the LHCII trimers is similar with qH ON/OFF based on their respective peaks overlaying each other after separation by gel filtration (Fig.…”
Section: Less Qh In Isolated System Compared To Intact Onesmentioning
confidence: 86%
“…Furthermore, fluorescence lifetimes of pigment-protein complexes largely depend on their local environment, e.g. detergent or proteoliposome (Tietz et al, 2020, Crepin et al, 2021, Nicol & Croce, 2021), and comparison of LHCII in detergent micelles vs. membrane nanodiscs shows that quenching is attenuated by detergent (Son et al, 2020). Another possible explanation for the differences in fluorescence lifetimes among sample types is that a preserved membrane macroorganisation is required for a full qH response; indeed LH1 and LH2 antenna rings in purple bacteria display a 50% shorter lifetime in vivo compared to in vitro (Ricci et al, 1996), and similarly quenching in LHCII is dependent on its membrane environment (Moya et al, 2001, Natali et al, 2016, Saccon et al, 2020, Manna et al, 2021).…”
Section: Discussionmentioning
confidence: 99%